2021
DOI: 10.1063/5.0039069
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of spin–orbit torque in WTe2/perpendicular magnetic anisotropy heterostructures

Abstract: Spin–orbit torque (SOT), exerted to a ferromagnet from an adjacent non-magnetic layer, has been widely considered as a promising strategy to realize spintronic devices with high energy efficiency, endurance, and speed. Much effort has been devoted to the search for materials and structures that can generate strong SOTs. Recent investigations showed that two-dimensional (2D) transition metal dichalcogenides provide the potential to produce strong enough SOTs to manipulate the magnetic devices due to rich spin-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[ 12,13 ] It has been reported in the literature that magnetic ordering has been detected in 2D materials with long spin relaxation times and spin diffusion lengths. [ 5,14 ] 2D TMDs with strong spin–orbit coupling can generate large magnetic anisotropy and band splitting to suppress thermal perturbation effects and thus maintain long‐range magnetic coupling. These materials have intrinsic long‐range magnetic order, and their magnetic properties have a clear dependence on the number of layers, and when the thickness of the bulk system is reduced to the monolayer limit, they usually exhibit a significantly different magnetic behavior from the bulk and few‐layer samples.…”
Section: D Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…[ 12,13 ] It has been reported in the literature that magnetic ordering has been detected in 2D materials with long spin relaxation times and spin diffusion lengths. [ 5,14 ] 2D TMDs with strong spin–orbit coupling can generate large magnetic anisotropy and band splitting to suppress thermal perturbation effects and thus maintain long‐range magnetic coupling. These materials have intrinsic long‐range magnetic order, and their magnetic properties have a clear dependence on the number of layers, and when the thickness of the bulk system is reduced to the monolayer limit, they usually exhibit a significantly different magnetic behavior from the bulk and few‐layer samples.…”
Section: D Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…Recently, the hybrid between 2D vdW materials with HM/FM films has proved to be a good candidate for energy-efficient SOT devices (Xie et al, 2019;Debashis et al, 2020;Lv et al, 2021). It was experimentally demonstrated that the SOT efficiency in Pt/ (Co/Ni) 2 was 17 times enhanced by MoS 2 underlayer (Xie et al, 2019), but the underlying mechanisms need to be further investigated.…”
Section: Performance Modulation Of Conventional Sot Devices By 2d Vdw Materialsmentioning
confidence: 99%
“…Charge current injection along the low-symmetry a axis of WTe 2 generates an unconventional, out-of-plane anti-damping SOT, boldτADOOP, of the form boldmtruê×boldztruê×boldmtruê ( boldmtruê,boldztruê are unit vectors along ferromagnet magnetization and WTe 2 /ferromagnet interface) ( 28 , 29 ). This anti-damping-like torque, termed so as it acts against the ferromagnet’s intrinsic Gilbert damping from effective magneto-crystalline anisotropy field, can be used for field-free switching of PMA ferromagnets ( 24 – 26 , 30 ). Theoretical studies into the microscopic origin of the unconventional torque point to the spin-Hall effect as the major contributing factor ( 29 ).…”
Section: Introductionmentioning
confidence: 99%